2021
DOI: 10.1108/meq-10-2020-0218
|View full text |Cite
|
Sign up to set email alerts
|

Do economic endeavors complement sustainability goals in the emerging economies of South and Southeast Asia?

Abstract: PurposeIn the present study, the authors intended to investigate whether the economic growth drivers such as per capita income, financial development, nonrenewable energy solutions and trade expansion have invigorated the level of environmental pollution in the eight developing nations of South and Southeast Asia.Design/methodology/approachConsidering the possibility of the cross-sectional dependency, the authors employed relatively new econometric approaches, that is, the Westerlund cointegration test and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…This indicates that the connection between economic growth and CO2 emissions has the inverted U-shape of the Kuznets hypothesis in SSA. This result is consistent with the conclusion of other similar earlier studies in different countries (Amar, 2021;Sharif et al, 2020;Sharma et al, 2021b;Ulucak & Bilgili, 2018; Sharma et al, 2021a;Elbatanony et al, 2021;Sharma et al, 2021a;Jihuan Zhang, 2021;Arshed et al, 2021;Elbatanony et al, 2021;Sohag et al, 2019;Bousquet & Favard, 2005;Terrell, 2021;Xiong et al, 2018;He et al, 2017).…”
Section: Pmg/ardl Estimatorssupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates that the connection between economic growth and CO2 emissions has the inverted U-shape of the Kuznets hypothesis in SSA. This result is consistent with the conclusion of other similar earlier studies in different countries (Amar, 2021;Sharif et al, 2020;Sharma et al, 2021b;Ulucak & Bilgili, 2018; Sharma et al, 2021a;Elbatanony et al, 2021;Sharma et al, 2021a;Jihuan Zhang, 2021;Arshed et al, 2021;Elbatanony et al, 2021;Sohag et al, 2019;Bousquet & Favard, 2005;Terrell, 2021;Xiong et al, 2018;He et al, 2017).…”
Section: Pmg/ardl Estimatorssupporting
confidence: 94%
“…There is an expanding body of literature that examines the cogency of the conventional upturned U-shape EKC hypothesis in different nations (Amar, 2021;Sharif et al, 2020;Sharma et al, 2021b;Ulucak & Bilgili, 2018;. Some of them does not support the EKC hypothesis (Ansari, Ahmad, et al, 2020;Sharma et al, 2021a); others found N-shaped relationship (Elbatanony et al, 2021;Sharma et al, 2021a;Jihuan Zhang, 2021); U-shaped (Ansari, Ahmad, et al, 2020;Arshed et al, 2021;Elbatanony et al, 2021;Sohag et al, 2019); M-shaped (Bousquet & Favard, 2005;Terrell, 2021); S-shaped (Xiong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Stating differently, renewable energy may help in improving environmental quality but stock market development may once again damage it if stock market shocks are stronger than renewable energy shocks. The results of Pham et al's (2020) and Sharma et al' (2021) study also confirmed that the extensive usage of cleaner energy solutions helped to reduce the environmental footprint in the European and South and Southeast Asia countries, respectively.…”
Section: <Insert Table-6>mentioning
confidence: 80%
“…In this pursuit, it should also be remembered that the rise in technological innovation in the countries also captures the innovations in energy production sector, and these innovations might be reflected in the rising alternate energy solutions, i.e. renewable energy solutions (Sharma et al 2021, Zafar et al 2021. With the rise in the diffusion of renewable energy solutions in these nations, it can be expected that carbon emissions might demonstrate a download trend in the coming years.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Several studies in the past have examined the environmental implications of various factors and documented evidence across regions of the world (Sharma et al 2020 ; Sharma et al 2021b , 2021c ; Sharma et al 2021b ). This study, therefore, extends this by investigating the dynamic impact of EPU, social welfare, trade openness, total natural resource rents, and life expectancy on EF which is examined by the autoregressive distributed lag (ARDL) approach by the estimators of the pooled mean group (PMG), dynamic fixed effect (DFE), and mean group (MG) under the maximum likelihood estimation (MLE) developed by Pesaran et al ( 1999 ).…”
Section: Data Model and Econometrics Methodsmentioning
confidence: 99%